Cross-Border Central Bank Digital Currencies, Bank Runs and Capital Flows Volatility - Popescu, Adina (IMF Working Papers; Working Paper ;, 2022)
Central banks around the world are increasingly exploring central bank digital currencies (CBDCs). This paper investigates the possible impacts of cross-border CBDCs on capital flows and financial stability in a simple open economy extension of a classical model of bank runs, augmented with the presence of a credible foreign central bank, which issues an account-based interest bearing CBDC available to nonresidents. The paper finds that the presence of a foreign CBDC which acts as an international safe asset may increase the risk of financial disintermediation in the domestic banking sector, which can be accompanied by higher and more volatile capital flows.